Anakinra in Paediatric Rheumatology and Periodic Fever Clinics: Is the Higher Dose Safe? - Fingerhutová, Šárka; Jančová, Eva; Doležalová, Pavla (Frontiers in Pediatrics, 2022)
Anakinra has been increasingly used in off-label indications as well as dosing and mode of administration in the variety of inflammatory conditions. We aimed to review our clinical practice and compare treatment outcomes with published data. Clinical data from electronic records were retrospectively reviewed for patients treated with anakinra over the past 6 years for autoinflammatory diseases (AID). From 47 eligible patients (27 females), 32 were children. Macrophage activation syndrome was the indication for anakinra therapy in 42.6% patients. Systemic juvenile idiopathic arthritis was the most common underlying diagnosis (19/47) followed by the spectrum of autoinflammatory diseases. Off-label use was noted in 38.3% patients. Recommended dose was exceeded in 21 children (mean induction dose 5.1, highest dose 26.1 mg/kg/day) and 2 adults, 5 patients were treated intravenously. The mean treatment duration for SJIA was 1.4, for AID 2.2 years, for patients with higher anakinra dose 9.71 (19.3) months. The mean follow-up duration was 2.7 (1.7) years. Treatment was effective in the majority of SJIA and CAPS patients as well as those with MAS. Anakinra was well tolerated without any major adverse effects even in patients with long-term administration of higher than recommended doses including 2 infants treated with the dose over 20 mg/kg/day. Our results support early use of anakinra in the individually tailored dosing. In patients with hyperinflammation anakinra may be life-saving and may even allow for corticosteroid avoidance. Further studies are needed in order to set up generally accepted response parameters and define condition-specific optimal dosing regime.